Changing Energy Requirements in the Mediterranean Under Changing Climatic Conditions - George Demosthenous; Christos Zerefos; Panos Hadjinicolaou; Christos Giannakopoulos (Energies, 2009)
This study investigates the impacts of climate change on energy requirements in the Mediterranean. Energy requirements, especially for space heating and cooling, are closely linked to several weather variables, mainly air temperature. The analysis is based on daily temperature outputs from several regional climate models run at a resolution of 25 km × 25 km in the framework of EU project ENSEMBLES using the A1B emissions scenario. The impacts of changes in temperature on energy requirements are investigated using the concept of degree days, defined as the difference of mean air temperature from a base temperature. Base temperature should be chosen to coincide with the minimum energy consumption. In this way, changes in heating and cooling requirements between the reference and the future period are calculated and areas about to undergo large changes identified. These changes are calculated between a 30-year reference period 1961–1990 and a near future period 2021–2050 taking the ensemble mean of all regional climate models. The near-term future has been chosen instead of the frequently used end-of-the-century period to assist policy makers in their planning. In general, a decrease in energy requirements is projected under future milder winters and an increase under hotter summers.